Mental Health in Croatian Competing Adolescent Athletes: Insights from the SMHAT-1 Questionnaire - Katarina Sore; Frane Franic; Luka Androja; Ivana Batarelo Kokic; Darko Marcinko; Stipe Drmic; Valentin Zdravko Markser; Tomislav Franic (Psychiatry International)
This study examines the prevalence of mental health problems among Croatian adolescent competing athletes, with a focus on gender differences. Mental health issues such as anxiety, depression, sleep disorders, and attention deficiency hyperactivity disorder (ADHD) are particularly relevant in this population due to the combined and simultaneous challenges of competitive sport and adolescence. Understanding gender-specific patterns is crucial for targeted interventions. A cross-sectional study involved 674 Croatian athletes (418 men, 256 women) aged 16–24 years from 43 sports. Data were collected using the Sports Mental Health Assessment Tool (SMHAT-1), which assessed 12 mental health concerns. Descriptive statistics, chi-square tests, effect size analysis with Cramér’s V, and power analysis were performed. The results showed significant gender-specific differences. Female athletes reported higher rates of anxiety (22.7% vs. 3.8%, p < 0.001), depression (25.4% vs. 5.3%, p < 0.001), alcohol use (27.0% vs. 7.7%, p < 0.001), ADHD (18.8% vs. 2.4%, p < 0.001), and post-traumatic stress disorder (8.2% vs. 1.2%, p < 0.001) compared to males. Gender-specific mental health interventions are crucial for improving sport performance and injury prevention. Further research should refine strategies to address vulnerabilities associated with gender and competitive sport environments.